Manipulation of multiple-responsive fluorescent supramolecular materials based on the inclusion complexation of cyclodextrins with Tyloxapol1. Issue 31 (21st August 2015) - Shen, Jinglin; Pang, Jinyu; Kalwarczyk, Tomasz; Hołyst, Robert; Xin, Xia; Xu, Guiying; Luan, Xiaoyu; Yang, Yingjie
<x xml:space="preserve">Abstract</x> Response of a 100 mg mL−1 α-CD/15 mg mL−1 Tyloxapol hydrogel towards additives, pH, temperature and solvent.